2001
DOI: 10.4049/jimmunol.166.12.7090
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of IL-22 Binding Protein, a Natural Antagonist of IL-10-Related T Cell-Derived Inducible Factor/IL-22

Abstract: The class II cytokine receptor family includes the receptors for IFN-αβ, IFN-γ, IL-10, and IL-10-related T cell-derived inducible factor/IL-22. By screening genomic DNA databases, we identified a gene encoding a protein of 231 aa, showing 33 and 34% amino acid identity with the extracellular domains of the IL-22 receptor and of the IL-20R/cytokine receptor family 2-8, respectively, but lacking the transmembrane and cytoplasmic domains. A lower but significant sequence identity was found with other members of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
211
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 235 publications
(221 citation statements)
references
References 19 publications
8
211
1
1
Order By: Relevance
“…The protein, lacking the transmembrane and cytoplasmic domains of typical class II cytokine receptors, displays structural homology with the extracellular portion of IL-22R1 [155]. The purified protein migrated as a 35 to 45-kDa band on SDS-PAGE gels, suggesting existence of glycosylation.…”
Section: The Il-22/il-22bp Structure and Interfacesmentioning
confidence: 97%
See 3 more Smart Citations
“…The protein, lacking the transmembrane and cytoplasmic domains of typical class II cytokine receptors, displays structural homology with the extracellular portion of IL-22R1 [155]. The purified protein migrated as a 35 to 45-kDa band on SDS-PAGE gels, suggesting existence of glycosylation.…”
Section: The Il-22/il-22bp Structure and Interfacesmentioning
confidence: 97%
“…Indeed, bioinformatics analysis predicts five N-glycosylation sites (Asn-X-Thr/Ser) based on the protein amino acid sequence. The recombinant protein binds to and inhibits IL-22 activity in hepatocytes and intestinal epithelial cells [155]. Furthermore, cross-linking experiments revealed that the protein binds IL-22 and prevents the formation of IL-22/IL-22R1/IL-10R2 ternary complex [154].…”
Section: The Il-22/il-22bp Structure and Interfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…D'autre part, les effets de l'IL-22 peuvent être neutralisés in vivo grâce à l'expression de son récepteur soluble, l'IL-22 binding protein (IL-22BP). L'IL-22BP est exprimée dans les poumons, la peau, la rate et le côlon [11] [12]. Ces observations ajoutent un niveau de complexité supplémen-taire dans la régulation fonctionnelle de l'IL-22 et pourraient rendre compte des résultats divergents rapportés dans les modèles de greffe allogénique de cellules hématopoïétiques et d'inflammation.…”
unclassified